Electronic structure of ferromagnetic heavy fermion, YbPdSi, YbPdGe, and YbPtGe studied by photoelectron spectroscopy, x-ray emission spectroscopy, and DFT + DMFT calculations. (2nd November 2017) - Yamaoka, Hitoshi; Thunström, Patrik; Tsujii, Naohito; Katoh, Kenichi; Yamamoto, Yoshiya; Schwier, Eike F; Shimada, Kenya; Iwasawa, Hideaki; Arita, Masashi; Jarrige, Ignace; Hiraoka, Nozomu; Ishii, Hirofumi; et al.
Abstract: Electronic structures of ferromagnetic heavy fermion Yb compounds of YbPdSi, YbPdGe, and YbPtGe are studied by photoelectron spectroscopy around the Yb 4 d –4 f resonance, resonant x-ray emission spectroscopy at the Yb L 3 absorption edge, and density functional theory combined with dynamical mean field theory calculations. These compounds all have a temperature-independent intermediate Yb valence with large Y b 3 + and small Y b 2 + components. The magnitude of the Yb valence is evaluated to be YbPtGe < YbPdGe ≲ YbPdSi, suggesting that YbPtGe is the closest to the quantum critical point among the three Yb compounds. Our results support the scenario of the coexistence of heavy fermion behavior and ferromagnetic ordering which is described by a magnetically-ordered Kondo lattice where the magnitude of the Kondo effect and the RKKY interaction are comparable.